MANAGEMENT ASPECTS OF CAPITALIZATION IN MODERN CONDITIONS OF ENTERPRISE ACTIVITIES - N. V. Shevchuk; O. V. Terentieva; S. M. Klymenko; V. P. Hmyria (Scientific Journal of Pedagogy and Economics, 2019)
The article presents the results of a critical analysis of scientific positions on the interpretation of the content of capitalization, which were streamlined in the following approaches: process, resource, value, analytical, relational, cognitive. Based on the integration of various research aspects of the definition of capitalization, the authors logic of interpreting its managerial nature has been formed, which is disclosed on the basis of the interrelationship of the set of processes (turning the capabilities of the external environment into enterprise resources, activating resources, productive use of resources, turning cost flows into capital) and objects (organizational abilities, resources, assets), the priority impact on which ensures the growth of business value. The value aspects of capitalization are investigated on the basis of the fundamental value approach, which made it possible to determine systems of critical points and monitoring indicators that signal the state of capital management of enterprises. The results of the implementation of the proposed analytical model of capitalization in the practice of the engineering enterprises of Ukraine are presented. On the basis of assessments of critical points of the strategic level of analysis, the main reasons affecting the dynamics of changes in the value of the studied enterprises are determined. Taking into account the specifics of the development of the business environment in the modern conditions of activity of machine-building enterprises, it was concluded that the value level of capital formation depends on the level of intellectualization and digitalization of production. Within the framework of the new technological paradigm, it is appropriate to develop the machine-building production according to the principles of the Industry 4.0 concept. In accordance with it, changes in the transformation of the way business processes are organized into digital factories are updated, which leads to the acquisition by enterprises of such characteristics as: the rate of customization of reactions to market demands ; digital certification; organization of activities on the principles of system engineering, etc.